Analysis of distributed energy resources for domestic electricity users - Raji, Atanda; Kahn, Mohamed Tariq (Journal of Energy in Southern Africa, 2012)
After over a century with utilization of the benefits of economics of scale, power systems planning and development gets bigger and transmission grids have needed to transmit wide bringing the concept of onsite or close-to-load generation back. The turnaround strategy is prompted by market liberalization, transmission expansion constraints, related technology advancements, environmental pollution, health hazards, fossil fuel depletion, and climate change concerns. In the last decade, many countries have started the process of liberalisation of the electric systems, opening access to transmission and distribution grids.Technical feasibility analysis of a hybrid energy system for two types of geographical regions in South Africa using Homer is performed in this paper. Wind-PV hybrid systems are modelled as a micro-power system using Homer. The simulation results analyses conducted for a typical middle income earner electricity load profile for both a coaster and inlander domestic users of electricity showed that Wind-PV hybrid system is technically feasible and economical.